Relational Network Theory as a bridge between linguistics and neuroscience: An interview with Professor Sydney Lamb - García, Adolfo Martín (2013)
Sydney Lamb is the creator and main developer of Relational Network Theory (RNT), a neurocognitive model of language. The theory’s major manifesto, titled Pathways of the Brain, was published in 1999. In several conferences given since then, Lamb has introduced a number of refinements, most of which have not appeared in print. Besides, Pathways of the Brain leaves open several questions which prove crucial to the theory’s long-time followers and newcomers alike. In this interview, Professor Lamb discusses historical, technical, and practical aspects of RNT, addressing both recent innovations and recurring queries.